Gender‐specific transcriptomic response to environmental exposure in flemish adults. (8th May 2013) - De, Sam; van, Danitsja M.; Jennen, Danyel G.J.; Koppen, Gudrun; Den, Elly; Nelen, Vera; Schoeters, Greet; Baeyens, Willy; van, Joost H.M.; Kleinjans, Jos C.S.; van, Nicolas
<x xml:space="preserve">Abstract</x> Flanders, Belgium, is one of the most densely populated areas in Europe. The Flemish Environment and Health Survey (2002–2006) aimed at determining exposure to pollutants of neonates, adolescents, and older adults and to assess associated biological and health effects. This study investigated genome wide gene expression changes associated with a range of environmental pollutants, including cadmium, lead, PCBs, dioxin, hexachlorobenzene, p, p'‐DDE, benzene, and PAHs. Gene expression levels were measured in peripheral blood cells of 20 adults with relatively high and 20 adults with relatively low combined internal exposure levels, all non‐smokers aged 50–65. Pearson correlation was used to analyze associations between pollutants and gene expression levels, separately for both genders. Pollutant‐ and gender‐specific correlation analysis results were obtained. For organochlorine pollutants, analysis within genders revealed that genes were predominantly regulated in opposite directions in males and females. Significantly modulated pathways were found to be associated with each of the exposure biomarkers measured. Pathways and/or genes related to estrogen and STAT5 signaling were correlated to organochlorine exposures in both genders. Our work demonstrates that gene expression in peripheral blood is influenced by environmental pollutants. In particular, gender‐specific changes are associated with organochlorine pollutants, including gender‐specific modulation of endocrine related pathways and genes. These pathways and genes have previously been linked to endocrine disruption related disorders, which in turn have been associated with organochlorine exposure. Based on our results, we recommend that males and females be considered separately when analyzing gene expression changes associated with exposures that may include chemicals with endocrine disrupting properties. Environ. Mol. Mutagen. 54:574‐588, 2013. © 2013 Wiley Periodicals, Inc.